THE PRACTICE OF UNIVERSITY’S ACADEMIC TEACHING STAFF FORMATION AND PROFESSIONAL COMPETENCES DEVELOPMENT OF THE LECTURERS ABROAD - Igor N. Kim (Высшее образование в России)
The problem of professional competency assessment of the academic teaching staff is very important for all the higher educational institutions of the global educational system. There are special research centers for developing methodological recommendations and best practices with abroad list of criteria being a contributory factor for unbiased assessment of lecturer’s scientific, innovative and teaching potential in the USA and European Union countries. As for the Russian Federation, it should be noted that in terms of higher education institutions we rarely use assessment criteria to estimate the competency and expertise of academic teaching staff. Therefore it’s necessary to adopt the leading countries’ experience and implement it in the Russian higher educational institutions in order to estimate the effectiveness of lecturers’ teaching activities and foster his professional and career promotion.